(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2026)
This study examines the historical dynamics of crimes and offenses committed by women in Uzbekistan. The research draws on archival materials, statistical data, and academic literature to explore changes in female criminal activity during the years of independence. Particular attention is given to the socio-economic factors influencing women’s involvement in crime and the role of state policy in preventing such offenses. The findings suggest that the proportion of crimes committed by women has gradually decreased in recent years.